Analisis Kinerja Keuangan Pemerintah Daerah Sumatera Utara Pada Masa Pandemi Covid-19 - Yuni Lestari Br Sitepu; Munawarah Munawarah; Novita Lamria Simatupang (Fakultas Ekonomi Prodi Akuntansi, 2022)
This study aims to examine the financial performance of the North Sumatra Province government during the Covid-19 pandemic. The data is quantitative descriptive and the data is taken from the LRA 2020 and LRA 2021 North Sumatra Province which have been audited. The results obtained by the Province of North Sumatra remain independent even in the midst of a pandemic. Judging from the effectiveness ratio, the realization of North Sumatra Province Original Regional Revenue (PAD) in 2020 is 101.8% and in 2021 it is 101.95% of the PAD budget set. The operating expenditure compatibility ratio, namely a decrease in the expenditure ratio from 2020 to 2021. The Capital Expenditure Harmony Ratio experienced a decrease in Capital Expenditures in 2021 due to a reduction in capital expenditures consisting of equipment and machinery capital expenditures, building and building capital expenditures, road capital expenditures, Irrigation and Network and Other Fixed Assets Capital Expenditure. The income growth ratio in 2020 is -1.24% which shows that the income in North Sumatra Province is decreasing, and that income is increasing by 8.65% in 2021.